Lake Area Variability Across a Climatic and Vegetational Transect in Southeastern Alberta - Campbell, Celina; Campbell, Ian; Hogg, Edward (Géographie physique et Quaternaire, 1994)
ABSTRACTAreas of 34 small lakes forming a transect across the southern margin of the Boreal Forest into the Grassland in southern Alberta were obtained from 326 aerial photographs, with at least six photographs for each lake in different months and different years from 1949 to 1992. Standard deviations of standardised lake areas (used as an index of lake area sensitivity to short term climate fluctuations) were plotted against a climatic moisture index; the resulting scatter of points is constrained by a function relating lake sensitivity to long-term regional climatic moisture. The lakes show high sensitivity in the Grassland where potential évapotranspiration exceeds precipitation, a steep drop in sensitivity over a small range of climatic moisture values in the Aspen Parkland, and very low sensitivity in the Boreal Forest where precipitation exceeds potential évapotranspiration.